Community Participation In Implementing Pancasila Democratic Values - Fahmi, Rizal; Abdar, Yusrijal; Ridayani, Ridayani; Azis, Abdul (Universitas Syiah Kuala, 2024)
Indonesia Pancasila democracy is a democratic concept that combinesdemocratic principles with Pancasila values as a moral and ethicalbasis. This concept becomes important in the context of Indonesia, as a country that has social, cultural and religious diversity. Pancasila democracy emphasizes the implementation of active community activities in terms of decision-making and good and transparent governance. However, challenges in the implementation of Pancasila democracy remain, including strengthening the quality of political leadership, high levels of participation indecision making,and increasing government accountability. Pancasila democracy is a democratic concept that combines democratic principles with Pancasila values as a moral and ethical basis. In the Indonesian context, Pancasila democracy is expected to exemplify a positive impact on the life of the Indonesian people. The implications of implementing Pancasila democracy in the life of the nation and state are that it can strengthen national unity and integrity, strengthen the principles of social justice, increase government accountability, and improve the quality of life of the people. The good and effective implementation of Pancasila democracy is expected to provide better results for the lives of the Indonesian people, by upholding the principles of justice, equality and unity. Therefore, efforts must be made to foster public understanding of Pancasila democracy and to develop a better democratic system in Indonesia.